PVC concrete composites: comparative study with other polymer concrete in terms of mechanical, thermal and electrical properties - Ceran, Ozge Bildi; Simsek, Baris; Uygunoglu, Tayfun; Şara, Osman Nuri (Springer, 2019)
Recycling PVC wastes with conventional chemical recycling methods such as pyrolysis, gasification is not feasible due to the carbon dioxide and dioxin emmissions generated with these methods. PVC wastes can be disposed using in ready-mixed concrete which is the most commonly used building material. In this study, effects of waste PVC instead of fine aggregate and the effects of waste PVC on the concrete properties were analyzed using 0%, 30%, 35%, 40% and 45% (w/w) in the experiments. Effects of waste PVC in concrete were compared with the other waste polymer concrete in terms of mechanical, thermal and electrical properties. All waste polymers have reduced the mechanical strength of concrete as expected. Improvement rates for the splitting tensile strength for 28days are found to be 54.46%, 48.52% and 6.93% for PP, PET and rubberized concrete, respectively, in comparison with reference concrete. For thermal conductivity, improvement rates for 40% PC, 40% PP and 40% PVC concrete are found to be 52.56%, 44.87% and 42.31%, respectively. For electrical resistivity, the highest improvement rate was determined as 136.03%, 132.38% and 105.92% for PC, PVC and rubberized concrete, respectively.
Keywords: PVC concrete composite; Electrical resistivity; Thermal conductivity